Actively rotating granular particles manufactured by rapid prototyping - Scholz, Christian; Pöschel, Thorsten (Revista Cubana de Fisica, 2016)
We study actively rotating granular particles manufactured by rapid prototyping. Such particles, as introduced in Ref. [1], convert vibrational motion into rotational motion via tilted elastic legs in a circular arrangement at the bottom of the particle. We extend the original design of the particles to make them suitable for mass-fabrication via rapid prototyping. The rotational velocity is measured in dependence of the driving frequency and amplitude. We find two different regimes of motion. For small amplitudes the particle performs a slow and stable rotation, while above a certain threshold the particle starts to perform a precission and consequently rotates significantly faster.

Direct relations between morphology and transport in Boolean models - Scholz, Christian; Klatt, Michael; Mecke, Klaus; Wirner, Frank; Hirneise, Daniel; Schröder-Turk, Gerd; Bechinger, Clemens (Physical Review E, 2015)
We study the relation of permeability and morphology for porous structures composed of randomly placed overlapping circular or elliptical grains, so-called Boolean models. Microfluidic experiments and lattice Boltzmann simulations allowus to evaluate a power-lawrelation between theEuler characteristic of the conducting phase and its permeability. Moreover, this relation is so far only directly applicable to structures composed of overlapping grains where the grain density is known a priori. We develop a generalization to arbitrary structures modeled by Boolean models and characterized by Minkowski functionals. This generalization works well for the permeability of the void phase in systems with overlapping grains, but systematic deviations are found if the grain phase is transporting the fluid. In the latter case our analysis reveals a significant dependence on the spatial discretization of the porous structure, in particular the occurrence of single isolated pixels. To link the results to percolation theory we performed Monte Carlo simulations of the Euler characteristic of the open cluster, which reveals different regimes of applicability for our permeability-morphology relations close to and far away from the percolation threshold.

Erratum: Publisher Correction: Rotating robots move collectively and self-organize (Nature communications (2018) 9 1 (931)) - Scholz, Christian; Engel, Michael; Pöschel, Thorsten (Nature Communications, 2018)
The original version of this Article contained an error in Fig. 5. In Fig. 5e, the scale on the y-axis originally incorrectly went from '0' to '1.10-4'. The correct scale goes from '0' to '0.4'. In Fig 5f, the x-axis labels were incorrectly shifted to the right. This has been corrected in both the PDF and HTML versions of the Article.
CRIS-Team Scopus Importer:2021-12-22

Erratum to: Actively Rotating Granular Particles Manufactured by Rapid Prototyping - Scholz, Christian; Pöschel, Thorsten (Revista Cubana de Fisica, 2016)
In [1] the rotational frequency of a single Vibrot was incorrectly plotted as a function of the excitation amplitude A. Instead the figure shows the data in dependence of the dimensionless acceleration Γ= A(2πƒD)2/g, where g is the gravitational acceleration. Only in the case of ƒD = 50 Hz A = 0.13 mm corresponds to Γ = 1.3 g and vice versa. The corresponding paragraph of the original manuscript must then be replaced by the following: „Figure 4 shows ϖ vs. ƒD for two different values of the dimensionless acceleration Γ = A(2πƒD)2/g. For a low Γ the particle performs slow rotation where ƒD depends non-monotonously on the frequency characterized by a minimum at ƒD = 50 Hz. For large Γ, we observe slow rotation at low frequency and tumbling motion for ƒD ≥ 30 Hz, where the rotational velocity decreases with increasing ƒD.“ The corrected version of the plot is shown in Fig. 4.

Inexpensive Mie scattering experiment for the classroom manufactured by 3D printing - Scholz, Christian; Sack, Achim; Heckel, Michael; Pöschel, Thorsten (European Journal of Physics, 2016)
Scattering experiments are fundamental for structure analysis of matter on molecular, atomic and sub-atomic length scales. In contrast, it is not standard to demonstrate optical scattering experiments on the undergraduate level beyond simple diffraction gratings. We present an inexpensive Mie scattering setup manufactured with 3D printing and open hardware. The experiment can be used to determine the particle size in dilute monodisperse colloidal suspensions with surprisingly high accuracy and is, thus, suitable to demonstrate relations between scattering measurements and microscopic properties of particles within undergraduate lab course projects.
Keywords: Mie scattering; physics education experiments; 3D printing; open hardware

Pattern-fluid interpretation of chemical turbulence - Scholz, Christian; Schröder-Turk, Gerd; Mecke, Klaus (Physical Review E, 2015)
The spontaneous formation of heterogeneous patterns is a hallmark of many nonlinear systems, from biological tissue to evolutionary population dynamics. The standard model for pattern formation in general, and for Turing patterns in chemical reaction-diffusion systems in particular, are deterministic nonlinear partial differential equations where an unstable homogeneous solution gives way to a stable heterogeneous pattern. However, these models fail to fully explain the experimental observation of turbulent patterns with spatio-temporal disorder in chemical systems. Here we introduce a pattern-fluid model as a general concept where turbulence is interpreted as a weakly interacting ensemble obtained by random superposition of stationary solutions to the underlying reaction-diffusion system. The transition from turbulent to stationary patterns is then interpreted as a condensation phenomenon, where the nonlinearity forces one single mode to dominate the ensemble. This model leads to better reproduction of the experimental concentration profiles for the "stationary phases" and reproduces the turbulent chemical patterns observed by Q. Ouyang and H. L. Swinney [Chaos 1, 411 (1991)].

Ratcheting and tumbling motion of Vibrots - Scholz, Christian; Dsilva, Sean; Pöschel, Thorsten (New Journal of Physics, 2016)
Systems of granular rotors (Vibrots), that is, small devices that convert linear vibrational motion into rotation by frictional impact, are of scientific interest since they could reveal various types of collective behavior. Looking at an isolated Vibrot, we note at least two dierent dynamical modes, depending on the parameters of the vibrational driving. By means of Finite Element simulations, we reveal the driving mechanism for both cases which may be correspondingly identified as ratcheting and tumbling. The transition between both modes resembles period doubling in certain bouncing ball problems leading eventually to chaotic motion in such systems.

Rotating robots move collectively and self-organize. - Scholz, Christian; Engel, Michael; Pöschel, Thorsten (Nature Communications, 2018)
Biological organisms and artificial active particles self-organize into swarms and patterns. Open questions concern the design of emergent phenomena by choosing appropriate forms of activity and particle interactions. A particularly simple and versatile system are 3D-printed robots on a vibrating table that can perform self-propelled and self-spinning motion. Here we study a mixture of minimalistic clockwise and counter-clockwise rotating robots, called rotors. Our experiments show that rotors move collectively and exhibit super-diffusive interfacial motion and phase separate via spinodal decomposition. On long time scales, confinement favors symmetric demixing patterns. By mapping rotor motion on a Langevin equation with a constant driving torque and by comparison with computer simulations, we demonstrate that our macroscopic system is a form of active soft matter.

Velocity distribution of a homogeneously driven two-dimensional granular gas - Scholz, Christian; Pöschel, Thorsten (Physical Review Letters, 2017)
The theory of homogeneously driven granular gases of hard particles predicts that the stationary state is characterized by a velocity distribution function with overpopulated high-energy tails as compared to the exponential decay valid for molecular gases. While this fundamental theoretical result was confirmed by numerous numerical simulations, an experimental confirmation is still missing. Using self-rotating active granular particles, we find a power-law decay of the velocity distribution whose exponent agrees well with the theoretic prediction.